Effect of P2Y12 inhibitors on thrombus stability and endogenous fibrinolysis. Issue 173 (January 2019) - Spinthakis, Nikolaos; Farag, Mohamed; Gue, Ying X.; Srinivasan, Manivannan; Wellsted, David M.; Gorog, Diana A.
Abstract: Although used routinely to reduce thrombotic events in patients with coronary disease, the effects of P2Y12 inhibitors on thrombus stability and endogenous fibrinolysis are largely unknown. Blood taken from patients pre- and post-aspirin ( n  = 20) and on aspirin alone and on dual antiplatelet therapy comprising aspirin plus clopidogrel ( n  = 20), ticagrelor (n = 20) or cangrelor (n = 20), was tested using the Global Thrombosis Test. The number of "rebleeds" or drops (D) after early platelet-rich thrombus formation (occlusion time, OT), and before final lasting occlusion, was used as an inverse measure of thrombus stability. Whilst clopidogrel had no effect, ticagrelor and cangrelor both increased D significantly, reflecting increased thrombus instability [D pre- and post-clopidogrel 4.3 ± 1.6 vs. 4.5 ± 1.4, p   =  0.833; pre- and post-ticagrelor 4.1 ± 2.4 vs. 6.8 ± 5.1, p   =  0.048; pre- and post-cangrelor 3.6 ± 2.0 vs. 7.9 ± 8.9, p  = 0.046]. Platelet reactivity was reduced by all P2Y12 inhibitors, demonstrated by OT prolongation (clopidogrel 378 ± 87 s vs. 491 ± 93 s, p  < 0.001; ticagrelor 416 ± 122 s vs. 549 ± 121 s, p  < 0.001; cangrelor 381 ± 146 s vs. 613 ± 210 s, p < 0.001). The magnitude of OT prolongation compared to baseline (ΔOT) was significantly greater for cangrelor compared to clopidogrel and ticagrelor. Cangrelor was the only agent to enhance fibrinolysis (lysis time pre- and post-cangrelor 1622[1240–2048]s vs. 1388[960–1634]s, p   =  0.005). We demonstrate the ability to assess the effect of pharmacotherapy on thrombus stability in vitro and show that P2Y12 inhibitors potentiate thrombus instability at high shear. Cangrelor, and to a lesser extent ticagrelor, de-stabilised thrombus formation and cangrelor also enhanced fibrinolysis. Potentiation of thrombus instability could become a new pharmacological target, that may be particularly important in acute coronary syndromes. Highlights: What is known on this topic Thrombus stability, the ability to withstand embolization and fibrinolysis, is an important determinant of infarction Prior studies of thrombus stability with perfusion chambers utilise citrated blood which inhibits the effect of thrombin The effects of P2Y12 inhibitors on thrombus stability and endogenous fibrinolysis are largely unknown Antithrombotic agents have shear-dependent effects and may increase thrombus fragility or enhance endogenous fibrinolysis What this paper adds P2Y12 inhibitors affect thrombus stability under high shear, in non-citrated blood, using a point-of-care technique Clopidogrel, ticagrelor and cangrelor, with aspirin, but not aspirin alone, inhibit shear-induced platelet reactivity The magnitude of effect is greatest for cangrelor, followed by ticagrelor, and clopidogrel Cangrelor and ticagrelor significantly de-stabilize thrombus formation and cangrelor also enhanced endogenous fibrinolysis Potentiation of thrombus instability could become a new pharmacological target, particularly in acute coronary syndromes